Peran Gereja Dalam Mewujudkan Perdamaian Dunia Perspektif Oikumene Berdasarkan 2 Korintus 5:18-20 - Esron Siregar; Dewi Dewi; Nuryani Nuryani; Netsen Netsen (Jurnal Kala Nea, 2025)
This article discusses the role of the church in realizing world peace from an ecumenical perspective based on the study of the text 2 Corinthians 5: 18-20. Indonesia cares about world peace and is active in realizing it, as evidenced by the regulations seen in the Preamble of the 1945 Constitution, because world peace is a shared responsibility. Seeing the prolonged conflicts that can be caused by differences in religious doctrines, religions, ethnicities, cultures, and politics will continue to exist if not addressed wisely. What is even more saddening is that conflicts actually occur within the church, related to differences in doctrine, liturgy, and personal interests, which are rampant within the church. In fact, it is in the church that the teachings of justice and love have always been at the forefront of the church's proclamation. Through qualitative methods with an interpretative approach, the true meaning of peace and the church's active role in realizing world peace will be discovered. The result shows that the role of the church is to proclaim that Christ is the mediator of reconciliation and that peace has been accomplished by Him. God loves the world that prays without counting human transgressions, even making Himself the redeemer of human sins. Thirdly, God entrusts the message of reconciliation to be carried out by humans and makes them God's messengers in proclaiming peace. The Ecumenical perspective emphasizes the importance of interdenominational cooperation to create church unity in support of universal peace. Furthermore, this research emphasizes that the church not only functions as a religious institution but also plays the role of a close friend in a pluralistic society. Only through Christ can true reconciliation be achieved, both within the church community and throughout the diverse world. In response to the challenges faced by the world today, this article suggests that the church be more active in spreading the values of the Kingdom of God and becoming a tangible embodiment of the message of shalom.